Gender quotas in the board room and firm performance: Evidence from a credible threat in Sweden - Björn Tyrefors Hinnerich; Joakim Jansson (Research Institute of Industrial Economics (IFN), 2017)
Board room quotas have recently received an increasing amount of attention. This paper provides novel evidence on firm performance from an exogenous change in female board participation in Sweden. We use the credible threat, aimed at listed firms, of a quota law enacted by the Swedish deputy prime minister as an exogenous variation. The threat caused a substantial and rapid increase in the share of female board members in firms listed on the Stockholm stock exchange. This increase was accompanied by an increase in different measures of firm performance in the same years, which were related to higher sales and lower labor costs.
Keywords: G34; G38; J16; J48; J78; M12; M51; 330; Gender quotas; Corporate boards; Firm performance